Evaluating tasks within a high‐probability request sequence in children with autism spectrum disorder. (7th August 2018) - Planer, Jilian; DeBar, Ruth; Progar, Patrick; Reeve, Kenneth; Sarokoff, Randi
Abstract: Noncompliance is common in children with autism spectrum disorder (ASD). Antecedent interventions offer effective alternative to consequence procedures to decrease noncompliance. Although high‐probability request sequences have been shown to be effective, previous research has not evaluated types of tasks within a high‐probability request sequence. We compared the effects of relevant and irrelevant high‐probability tasks on compliance to low‐probability (low‐ p ) requests in children with ASD. After high levels of compliance to low‐ p tasks were achieved across relevant and irrelevant conditions, fixed and variable presentations of high‐probability requests were compared. Results showed that relevant high‐probability requests increased the percentage of compliance more than irrelevant high‐probability requests across participants as compared with baseline. For two of three participants, variable presentations of the high‐probability requests resulted in higher percentages of compliance than fixed presentations. Results suggest that a variable presentation of relevant tasks should be considered within the high‐probability request sequence.